Effect of Intraoperative Glucose Infusion on Catabolism of Adipose Tissue and Muscle Protein in Patients Anesthetized With Remifentanil in Combination With Sevoflurane During Major Surgery: A Randomized Controlled Multicenter Trial. (October 2016) - Sawada, Atsushi; Kamada, Yasuhiro; Hayashi, Haruko; Ichinose, Hiromichi; Sumita, Shinzo; Yamakage, Michiaki
Abstract : BACKGROUND: A harmful effect of stress hormone secretion during surgery is lipolysis and proteolysis to maintain normal blood glucose levels. A well-titrated general anesthetic improves blood glucose control by suppressing secretion of these stress hormones. The aim of this study was to explore the effect of intraoperative glucose infusion on lipolysis and proteolysis in patients undergoing a general anesthetic consisting of sevoflurane and remifentanil during long (>6 hours) major surgery. METHODS: In this prospective, single-blinded, randomized, multicenter trial, 80 patients with an expected duration of anesthesia of >6 hours were allocated to either the glucose group, consisting of 40 patients who were infused with acetated Ringer's solution with glucose (2 mg/kg/min), or the no glucose group, consisting of 40 patients who were infused with the same solution, but without glucose. After oxygenation, general anesthesia was induced with propofol, fentanyl, and rocuronium and was maintained with sevoflurane, oxygen, rocuronium, and remifentanil infusions. The rates of remifentanil infusion were titrated based on systolic arterial blood pressure, maintaining this parameter within 10% of its postanesthesia values. Seventy-four patients completed the study. Urinary 3-methylhistidine/creatinine (3-MH/Cre) ratio, acetoacetic acid, 3-hydroxybutyric acid, blood glucose, insulin, and cortisol were measured 3 times: at anesthesia induction (0 hour) and at 3 and 6 hours after anesthesia induction. Urinary 3-MH/Cre ratio was the primary study outcome. RESULTS: In the no glucose group, the urinary 3-MH/Cre ratio at 6 hours was increased compared with that at 0 hour (213 [range, 42–1903] vs 124 [18–672] nmol/μmol; the difference in medians, 89; the 95% confidence interval [CI] of the difference, 82–252; P = .0002). Acetoacetic acid and 3-hydroxybutyric acid levels in the no glucose group were greater than those in the glucose group at 6 hours (110 [8–1036] vs 11 [2–238] μmol/L; the difference in medians, 99; the 95% CI of the difference, 92–196; P < .0001 and 481 [15–2783] vs 19 [4–555] μmol/L; the difference in medians, 462; the 95% CI of the difference, 367–675; P < 0.0001, respectively). Blood glucose and insulin levels in the glucose group were greater than those in the no glucose group at 3 hours (146 [103–190] vs 93 [72–124] mg/dL; the difference in medians, 53; the 95% CI of the difference, 47–55; P < .0001 and 9.8 [1.2–25.4] vs 3.2 [0.4–15.0] μU/mL; the difference in medians, 6.5; the 95% CI of the difference, 4.8–6.8; P < .0001) and 6 hours (139 [92–189] vs 87 [68–126] mg/dL; the difference in medians, 52; the 95% CI of the difference, 44–58; P < .0001 and 8.1 [1.2–22.3] vs 3.2 [0.4–10.1] μU/mL; the difference in medians, 4.9; the 95% CI of the difference, 4.0–5.9; P < .0001). Cortisol levels in both groups were similarly within normal levels at 0, 3, and 6 hours. CONCLUSIONS: The study showed that intraoperative glucose infusion suppressed lipolysis and proteolysis in patients anesthetized with remifentanil in combination with sevoflurane during surgery of >6 hours in length.